The Effect of Clarity of Budget Targets and Reporting System on Performance Accountability with Internal Control as Intervening Variables in SKPD Kotabaru District Government - SANUSI, Sanusi; RIYADI, Padlah (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:Financial Reporting System, In the public sector, financial reports have an important role in generating accountability. The financial information contained in the financial statements becomes the basis for considering decisions. Financial information as a tool to carry out public accountability as effectively as possible, and is not included as the final goal of public sector accounting.Methodology:This study aims to examine the clarity of budget targets and reporting systems that affect performance accountability. This study also examines whether the internal control system mediates the effect of the clarity of budget targets and the reporting system. This study is of the type of associative causality and is carried out through a survey method by distributing questionnaires to the compilers of the performance accountability report of government agencies in Kotabaru.Findings:The population of this study was all SKPD in the Kotabaru Regency Government, totalling 30 SKPD consisting of 82 sample respondents. This study uses descriptive statistical analysis and partial least squares (SEM-PLS) analysis. Analysis powered by Smart-PLS 3.0.Implication:The results of this study show that the clarity of budget targets and internal controls affect the performance accountability of government agencies, while the reporting system does not affect performance accountability. Clarity of budget targets, and reporting systems affect internal control. Internal control as an intervening variable can affect the clarity of budget objectives and reporting systems on performance accountability.